Trauma dan Penerimaan Diri Tokoh Utama dalam Seporsi Mie Ayam Sebelum Mati Berdasarkan Rogers dan Herman - Risa risa; Anas Ahmadi Anas (Kande : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the forms of trauma and the process of self-acceptance experienced by Ale, the main character in Brian Khrisna's novel Seporsi Mie Ayam Sebelum Mati (2025), by integrating Carl Rogers' humanistic psychology and Judith Herman's trauma theory. Using a literary psychology approach and descriptive qualitative methods, this study analyzes narrative expressions, dialogues, and monologues that reveal Ale's psychological wounds and his gradual recovery process. The research findings indicate that Ale experienced multidimensional trauma rooted in childhood rejection, verbal abuse, emotional neglect, bullying, and social betrayal. These experiences created a self-discrepancy as described by Rogers, and a loss of security as proposed by Herman. Both conditions significantly affected Ale's self-concept, self-esteem, and sense of meaning in life. His healing process emerged through emotional security, empathetic encounters, and supportive relationships with supporting characters. The analysis demonstrates the relevance of Herman's three stages of recovery security, remembering and mourning, and reconnection, which align with Rogers's ideas of self-awareness, unconditional acceptance, and self-actualization. This research confirms the novel as a representation of psychological trauma as well as a literary medium that depicts the human capacity to recover through acceptance and empathetic interpersonal relationships, and contributes to literary psychology through an integrative theoretical perspective. Keywords: Trauma, Self-Acceptance, Carl Rogers, Judith Herman, Novel A Portion of Chicken Noodles Before Dying.